2012
DOI: 10.1007/s10120-012-0142-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of patient surveillance after curative gastrectomy for gastric cancer: a brief review

Abstract: Background Complete resection of a gastric cancer and adjacent lymph nodes offers the only chance for cure of the disease. However, disease recurrence occurs in 22-51% of cases, and its prognosis is very poor. Many clinicians perform post-operative follow-up for these patients, although there is no consensus on the regimen, frequency of visits, mode of testing, or the rationale of a follow-up program. Purpose The objective of this systematic review was to identify the evidence for surveillance in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 11 publications
1
36
0
Order By: Relevance
“…Cardoso et al[43] published a systematic review on this topic in 2012. In this study, the authors searched the literature from 1999 to 2009 and selected five retrospective studies that reported data on follow-up after gastric resection and included a total of 810 patients[44-48].…”
Section: What Is the Evidence?mentioning
confidence: 99%
“…Cardoso et al[43] published a systematic review on this topic in 2012. In this study, the authors searched the literature from 1999 to 2009 and selected five retrospective studies that reported data on follow-up after gastric resection and included a total of 810 patients[44-48].…”
Section: What Is the Evidence?mentioning
confidence: 99%
“…A recent systematic review by Cardoso et al [52] reviewed five studies enrolling a total of 810 patients and assessing outcomes of follow-up after gastrectomy for gastric cancer. They did not find any evidence suggesting that postoperative surveillance has any survival benefit; it is also stressed that no studies addressed quality of life issues.…”
Section: Evidence From Follow-up Studiesmentioning
confidence: 99%
“…Asymptomatic and symptomatic recurrence patterns are biologically different and associated with different survival outcomes Kim et al [14] Bilici et al [9] cancer, found that symptomatic recurrence is an important prognostic factor for post-recurrence survival and that presence of symptoms may be considered a marker of biologic tumor aggressiveness, which is an important determinant of survival at the time of recurrence diagnosis during follow-up for gastric cancer. A recent systematic review by Cardoso et al reviewed five studies enrolling a total of 810 patients and assessing outcomes of follow-up after gastrectomy for gastric cancer [16].…”
Section: )mentioning
confidence: 99%